KEPATUHAN IBU UNTUK KUNJUNGAN BALITA KE POSYANDU DI MASA PANDEMI - Eva Arnas Febriyanti; Sri Rahayu; Septika Yani Veronica; Siti Maesaroh (STIKES MITRA RIA HUSADA, 2022)
According to the results of the Indonesian Basic Health Research (Riskesdas) in 2018, the proportion oftoddlers weighing was 54.6%. Indonesia recorded that in 2018 there were 283,370 Integrated Healthcare Centersand 173,750 (61.32%) declared as active Integrated Healthcare Centers. The results of the pre-survey conducted atthe Durian Integrated Healthcare Centers targeting toddlers were 175 with a coverage of 30.47 visits for toddlers.The research objective was to determine the correlation between maternal anxiety and compliance with toddler visitsduring the Pandemic at the Durian Integrated Healthcare Centers in Yukum Jaya Village of Central LampungRegency in 2021. This research type is quantitative research with a cross-sectional approach. The population in thisstudy was all toddlers at the Durian Durian Integrated Healthcare Center in Yukum Jaya Village of CentralLampung Regency, totaling 175 respondents. The sample in this study amounted to 64 respondents. The analysisused the chi-square statistical test. The research result showed that there was a correlation between maternalanxiety and compliance with toddler visits during the Pandemic at the Durian Integrated Healthcare Center inYukum Jaya Village of Central Lampung Regency (p-value 0.000 OR: 12,0). Based on the research that has beendone, it is recommended for hr Poncowati Public Health Center to make efforts to increase the utilization ofIntegrated Healthcare Center services for toddlers such as counseling and socialization about the benefits ofIntegrated Healthcare Center for Toddlers. Health workers are advised to continue to teach in the implementation ofhealth protocols so, the mothers and toddlers still feel protected. Keywords : Anxiety, Compliance, Integrated Healthcare Center, Covid-19 Pandemic